Effect of a nanotechnology-based foliar fertilizer on the yield and fruit quality in an apple orchard - Csihon, Á.; Gonda, I.; Holb, I. J. (International Journal of Horticultural Science, 2021)
Nutrient management is a determining element of the technology in fruit production. Significance of foliar fertilization has been increased continuously over the last years, as it can improve directly the vegetative and generative performance of the trees. In this study we aimed to evaluate the effect of a nanotechnology-based foliar fertilizer (Bistep) with 1, 3, and 5 l/ha dosages on the yield and fruit quality parameters in an apple orchard during 2016 and 2018. According to our results, crop load increased with 29% in the third year of the experiment with the application of 5 l/ha Bistep treatment compared to the control treatments. Fruit weight was also improved in each year, as values of fruit weight in all treatments were higher than the control one (3.0-13.0% growth). Fruit surface color increased with 2-18% due to the foliar fertilizer. During the three years, leaf length was 9.5-9.9 mm on the control trees, as 9.8-10.4 mm was measured on the fertilized ones. In conclusion, yield and fruit quality can be improved in apple orchard using a nanotechnology-based foliar fertilizer.